PENERAPAN METODE KISS PRINCIPLE PADA APLIKASI PENGINGAT SHALAT BERBASIS WEB DAN SELULER - Andhik Ampuh Yunanto; Febi Fidhiyanti Putri; Desy Intan Permatasari; Nailussa’ada; Fadilah Fahrul Hardiansyah; Umi Sa’adah; Adam Shidqul Aziz (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The five daily prayers are an obligation of worship for Muslims in the world. Prayers have a predetermined time schedule according to the teachings of the Prophet Muhammad SAW and have different schedules according to each region and region. As Muslims, it is obligatory to pray five times a day. In addition, we also have to always deepen these teachings. However, byPulsa as a new start-up company in the field of "Convert Credit" technology certainly has increasingly busy activities. Therefore, byPulsa anticipates delays in praying. Not only praying, but also following studies to always study the religion of Islam. So the Ceo at byPulsa also made an application to anticipate delays with several additional features. Even so, it turns out that the use of applications still requires a lot of interaction and is less efficient. So, an application must be made that can shorten or minimize interaction costs. Apart from this, byPulsa must also make applications that are used by employees as well as everyone with the minimum amount of interaction cost possible. So by using the kiss principle method, the author tries to perfect the application by applying the kiss principle method, the results can be seen, that the user feels more satisfied with the application after that this application is able to determine the prayer schedule according to the position the user is in or according to the area the user is in, this application can help and guide users in deepening their religion by following online studies and using features such as prayer beads, Islamic book recommendations, even Islamic podcasts. As well as the Kiss principle method used here, it functions to make it easier for users to interact with the application.